2011
DOI: 10.1128/aem.00577-11
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Inhibition of Germination of Coat-Deficient Bacterial Spores by Multivalent Metal Cations, Including Terbium (Tb 3+ )

Abstract: Release of dipicolinic acid (DPA) and its fluorescence with terbium (Tb 3؉ ) allow rapid measurement of the germination and viability of spores of Bacillus and Clostridium species. However, germination of coat-deficient Bacillus spores was strongly inhibited by Tb 3؉ and some other multivalent cations. Tb 3؉ also inhibited germination of coat-deficient Clostridium perfringens spores.Many Bacillus and Clostridium species can form dormant, resistant spores under conditions unfavorable for growth (24,25). These s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Thus, the next potential NaCl inhibition targets would be the yet-unidentified ion channels involved in rapid cation efflux (29,34,39) and/or the DPA excretion channels that seem to be at least in part encoded by the spoVA operon, although their organization and mode of action is not yet understood (17,34,40,41). In a previous study reporting inhibitory effects of multivalent metal ions on the germination of decoated B. subtilis spores, the authors proposed that these ions form complexes with DPA, which could then act as a plug for the DPA channels (42). Whether this would also be possible for monovalent ions is unclear, but ionic interactions would certainly be conceivable.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the next potential NaCl inhibition targets would be the yet-unidentified ion channels involved in rapid cation efflux (29,34,39) and/or the DPA excretion channels that seem to be at least in part encoded by the spoVA operon, although their organization and mode of action is not yet understood (17,34,40,41). In a previous study reporting inhibitory effects of multivalent metal ions on the germination of decoated B. subtilis spores, the authors proposed that these ions form complexes with DPA, which could then act as a plug for the DPA channels (42). Whether this would also be possible for monovalent ions is unclear, but ionic interactions would certainly be conceivable.…”
Section: Discussionmentioning
confidence: 99%
“…The results described above indicated that coat defects have significant effects on permeation of molecules, including water, into spores. To examine if this is also the case for other small molecules that are thought to exert their effects by acting at a spore's inner membrane just outside the spore's core, we examined spores' permeation by two compounds, Tb 3ϩ and dodecylamine, that can influ- ence spores' return to life in the process of germination (27,29,34). TbCl 3 at ϳ50 M is often used to monitor the progress of spore germination, by measuring DPA release via Tb-DPA complex formation (28).…”
Section: Resultsmentioning
confidence: 99%
“…TbCl 3 at ϳ50 M is often used to monitor the progress of spore germination, by measuring DPA release via Tb-DPA complex formation (28). TbCl 3 at 50 M only minimally inhibits the germination of intact spores but completely inhibits the germination of severely coat-defective spores (29). The mechanism for this inhibition has not been definitively established, but it has been suggested that Tb 3ϩ binds to DPA being released from the protein channel in spores' IM through which DPA is released and the Tb-DPA complex blocks this channel completely.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a few experiments, spores were germinated as described above but without Tb 3ϩ present from the initiation of germination. Instead, at various times after germination was initiated, aliquots of the germinating culture were centrifuged, the supernatant fluid was made 50 M in TbCl 3 and Tb-DPA fluorescence was measured as described previously (22). Spore germination was also routinely monitored at the end of germination incubations by phase-contrast microscopy.…”
Section: Methodsmentioning
confidence: 99%